2000
DOI: 10.1002/chin.200042250
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: The Future of Magnetic Data Storage Technology

Abstract: The Future of Magnetic Data Storage Technology -[14 refs.]. -(THOMPSON, D. A.; BEST, J. S.; IBM J. Res. Dev. 44 (2000) 3, 311-322; Almaden Res. Cent., IBM Res. Div., San Jose, CA 95120, USA; EN)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 1 publication
0
36
0
1
Order By: Relevance
“…Reading an entire archive, even periodically, greatly limits the scalability of network stores. (The growth in storage capacity has far outstripped the growth in storage access times and bandwidth [44]). Furthermore, I/O incurred to establish data possession interferes with on-demand bandwidth to store and retrieve data.…”
Section: Introductionmentioning
confidence: 99%
“…Reading an entire archive, even periodically, greatly limits the scalability of network stores. (The growth in storage capacity has far outstripped the growth in storage access times and bandwidth [44]). Furthermore, I/O incurred to establish data possession interferes with on-demand bandwidth to store and retrieve data.…”
Section: Introductionmentioning
confidence: 99%
“…Gurumurthi and Sivasubramaniam [2006] reported that within the thermal envelope, the response time of real workloads can be improved by 30-60% with a 10K increase of the RPM. Unfortunately, the disk drives rotating at speeds exceeding 20, 000 RPM have been researched but not commercialized due to heat generation, power consumption, noise, vibration and other problems in characteristics, and a lack of long term reliability [Thompson and Best 2000]. Therefore, it is a big challenge to design new disk drive architecture which could further advance disk performance.…”
Section: Design Constraintsmentioning
confidence: 99%
“…When this happens, the information stored in the particle randomly reverses itself at a rate far higher than that needed to provide reliable storage. There are a few techniques being researched as a means of staving off the superparamagnetic effect as long as possible 2 , but increases in performance beyond another order of magnitude are not expected to materialize [35].…”
Section: Hard Discsmentioning
confidence: 99%